Syrian students in Turkish higher education: A systematic review and thematic synthesis - Tom Parkinson (International Journal of Educational Research Open)
A large scholarly literature now exists concerning displaced Syrian students in the Turkish higher education system. This literature is multilingual, thematically diverse, and dispersed across several disciplines. No systematic review of this literature has been undertaken to date, and there is therefore a need for corpus-level work to summarise its characteristics and synthesise its key concerns and themes. Following a hybrid approach incorporating scoping review and thematic synthesis, this article summarises the state of this literature, before synthesising its key themes and debates, highlighting points of consensus and contradiction, and identifying limitations and gaps to inform further research in the field. The review reveals a broad range of rich, intersecting themes, but also identifies limitations including a lack of developed theory, a reliance on a limited range of qualitative methodologies, limited geographical coverage, and the absence of longitudinal and intervention-based studies. Addressing these limitations in future work will strengthen the interface between academic research and evidence-informed policy and practice to support refugee students.